ChemInform Abstract: Novel 2, 6‐Disubstituted Phenylboronic Compounds — Synthesis, Crystal Structures, Solution Behavior and Reactivity. Issue 40 (October 2015) - Adamczyk‐Wozniak, Agnieszka; Ejsmont, Krzysztof; Gierczyk, Blazej; Kaczorowska, Ewa; Matuszewska, Alicja; Schroeder, Grzegorz; Sporzynski, Andrzej; Zarychta, Bartosz
Abstract Reductive cyclization of 2, 6‐diformylbenzeneboronic acid gives a (hydroxymethyl)benzoxaborole.